Sunitinib in metastatic renal cell carcinoma: An ethnic Asian subpopulation analysis for safety and efficacy. Issue 3 (27th February 2014) - Lee, Se‐Hoon; Bang, Yung‐Jue; Mainwaring, Paul; Ng, Christina; Chang, John W‐C; Kwong, Philip; Li, Rubi K; Sriuranpong, Virote; Toh, Chee‐Keong; Yuan, Jinyu; Pitman Lowenthal, Susan; Chung, Hyun C
Abstract Aims We evaluated and compared the safety and efficacy of sunitinib in Asian and non‐Asian patients with metastatic renal cell carcinoma enrolled in a previously reported global expanded access program. Methods Previously treated and treatment‐naïve patients received open‐label sunitinib at a starting dose of 50 mg/day for 4 weeks, followed by 2 weeks off treatment, in repeated 6‐week cycles. Safety was assessed regularly, tumor measurements were performed per local practice, and survival data collected where possible. Results Data were available for 212 Asian patients from Asian sites (Asian‐A), 113 Asian patients from non‐Asian sites (Asian‐O) and 4046 non‐Asian patients. The most common grade 3/4 treatment‐related adverse events were neutropenia, thrombocytopenia, hand–foot syndrome, diarrhea, asthenia and fatigue. The incidence of many adverse events was greater in Asian‐A than in Asian‐O or non‐Asian patients. Sunitinib efficacy was comparable between Asian and non‐Asian patients, with an objective response rate of 18% versus 14%; median progression‐free survival of 8.7 versus 10.9 months; and overall survival of 18.9 versus 18.4 months, respectively. Conclusions Sunitinib demonstrated tolerable safety and similar efficacy in Asian and non‐Asian patients. Geographic differences in the reported frequency of specific adverse events were noted across Asian patients.